The use of value-clarification strategies in teaching social studies to fast learners (Grade V) - Boado, Paulita G.; Mabesa, Jacquelyn (Quezon City College of Education, University of the Philippines Diliman, 1975)
Rath's value-clarification strategies have been used in developing social studies concepts in fast learners. Nine lessons using the different strategies have been enriched to cover various evaluative processes suited for fast learners. A sample of a developmental plan is provided to serve as a model for teachers in using this program.
"October, 1975."
Thesis (Master of Arts in Teaching Special Education - Giftedness)--University of the Philippines, Diliman
Keywords: Gifted children -- Education (Elementary) -- Philippines; Social sciences -- Study and teaching (Elementary) -- Philippines; Moral education (Elementary) -- Philippines; Values clarification -- Philippines